(3GMJQa (BMATLAB 7s - (3eMehO, XGaQs ((3MdHs (3TYGY ddfTQ hGdYdhes, 2007)
(3jZWj gPG GdcJGH cGaI GdfhGMj GdCSGSjI dHQfGeL (BMATLAB (3HCSdhH JYdjej eeJY ef NdGd GdCeKdI, ceG jfGbT cGaI GdEecGfjGJ GdLOjOI aj CMOK EUOGQGJ (BMATLAB (3hjfGbT JcGed (BMATLAB (3eY dZGJ GdHQeLI (BC (3h(BFORTRAN (3h(BJava (3eeG jRjO ef bOQI (BMATLAB (3heQhfJg ef NdGd GdJYGed eY NhGQRejGJ hbhGYO eYWjGJ NGQLjI, hjJVef gPG GdcJGH JZWjI TGedI ddagQSI hGdMdhd GdTYGYjI hGdLHQ GdNWj aj (BMATLAB(3, ceG Cfg Zfj HGdCeKdI aj cGaI aUhdg EVGakI Edi JNUjU aUd cGed ef CLd CeKdI eJbOeI(B. (3jbpqOe gPG GdcJGH deSJNpOej (BMATLAB - (3ShGA cGfhG eHJOFjf Ce eJbOejf (B- (3OQhSkG JYdjejI ecKaI Yf ejRGJ (BMATLAB (3hHQeLJgs
1 2
Keywords: MATLAB 7; (3GdHQeLIs; (3GdMGSHGJ GdEdjcJQhfjIs -- (3dZGJs